Transformasi Perguruan Tinggi Islam Tradisional Menuju Perguruan Tinggi Islam Kewirausahaan - Sonita, Era; Helmi, Helmi; Henmaidi, Henmaidi; Nofialdi, Nofialdi (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2022)
The aim of the paper is to investigate the experience and to identify the drivers of the transformation of traditional Islamic Universities into Entrepreneurial Islamic Universities to ensure the sustainability of Islamic Universities in West Sumatra. Due to its wide scope, characteristics of Entrepreneurial University, this research study is limited and focuses on universities that provide students with access to business facilities, business relations for students, and the university's openness to collaboration with students. its external stakeholders. An analysis of the experience of the IAIN Bukittinggi infrastructure university in providing services to students, as well as collaboration between Islamic universities and local governments and entrepreneurs shows a flat trend. On the other hand, such a trend cannot be observed for establishing an Entrepreneurial University at IAIN Bukittinggi over the past 5 years. The survey results indicate the need for higher efforts to assist young entrepreneurs in building cooperative networks and strengthening the co-creation of knowledge with external stakeholders.